Strategies to access health and social services for English-speaking older adults in Quebec: A qualitative case study - Ethier, Alexandra; Carrier, Annie (Canadian Social Work Review, 2023)
Considering that French is the dominant language in Quebec, that relatively few francophone providers of health and social services are able to speak English, and that English-speaking older adults (OAs) have low levels of bilingualism, anglophone OAs are more likely than their francophone peers to face language barriers when accessing health and social services. However, little is known about the strategies English-speaking OAs put into place to overcome the difficulties encountered due to language barriers when they access these services. We therefore aimed to document the strategies used by English-speaking OAs when, due to language barriers, they faced difficulties in accessing health and social services. We conducted a qualitative case study with ten English-speaking OAs in the Eastern Townships in Quebec. Through interviews and document reviews, we collected data which we then analyzed thematically. We identified seven strategies used by English-speaking OAs: investigating for health- and access-related information in English, creating their own services, entering the health and social services system offered in French, entering the health and social services system with help from others, putting the responsibility of overcoming the language barrier on the provider, splitting that responsibility, and taking on the responsibility. Our results highlight a potential burden associated with the involvement of the English-speaking community in enabling English-speaking OAs to access health and social services. Keywords: access, health services, social services, official language minority, language barriers, strategies

The pathway to diagnosis of dementia for Francophones living in a minority situation - Garcia, Linda J.; McCLeary, L.ynn; Emerson, Victor; Léopoldoff, Hélène; Dalziel, William; Drummond, Neil; Cohen, Carole; Koehn, Sharon; Silvius, James (The Gerontologist, 2014)
Purpose of the Study: As the prevalence of dementia increases, the pressure to make early diagnoses also increases. Although patients must be able to identify the symptoms to access appropriate services, they may not be equally accessible to all citizens in a multicultural society. Health care professionals and patients may lack a common “first language.” This study explores the experience of francophone persons with dementia (PWD) and their caregivers during the peri-diagnostic period. Design and Methods: Individual interviews were undertaken to elicit information regarding symptoms, the role of the family and friends, and the access to formal services. Seven PWD and their caregivers who spoke French as their primary language but who lived in a primarily English-speaking region completed the interviews. Results and Implications: No single symptom seemed sufficient to alert participants that dementia might be present. Participants communicated that there was a dire need to inform the public about the signs of dementia; they spoke of the role of the family physician and the importance of having a long-standing relationship with a health professional. For some, having similar personal characteristics, such as language and culture, might accentuate the strength of the relationship and facilitate the process of diagnosis.

Access to dementia services in a minority situation: The case of Francophones in Ontario [infographic] - Garcia, Linda; Chomienne, Marie-Hélène; Cadieux, M.-A.; Farmanova, E.; McCleary, L.; Molnar, F.; Agapitos, M.; Dalziel, W.; Khoury, L.; French-Merkley, V.; Joanisse, J. (2014)